Collagen-Derived Di-Peptide, Prolylhydroxyproline (Pro-Hyp): A New Low Molecular Weight Growth-Initiating Factor for Specific Fibroblasts Associated With Wound Healing - Sato, Kenji; Asai, Tomoko T.; Jimi, Shiro (Frontiers in Cell and Developmental Biology, 2020)
Many cells and soluble factors are involved in the wound healing process, which can be divided into inflammatory, proliferative, and remodeling phases. Fibroblasts play a crucial role in wound healing, especially during the proliferative phase, and show heterogeneity depending on lineage, tissue distribution, and extent of differentiation. Fibroblasts from tissue stem cells rather than from healthy tissues infiltrate wounds and proliferate. Some fibroblasts in the wound healing site express the mesenchymal stem cell marker, p75NTR. In the cell culture system, fibroblasts attached to collagen fibrils stop growing, even in the presence of protein growth factors, thus mimicking the quiescent nature of fibroblasts in healthy tissues. Fibroblasts in wound healing sites proliferate and are surrounded by collagen fibrils. These facts indicate presence of new growth-initiating factor for fibroblasts attached to collagen fibrils at the wound healing site, where the collagen-derived peptide, prolyl-hydroxyproline (Pro-Hyp), is generated. Pro-Hyp triggers the growth of p75NTR-positive fibroblasts cultured on collagen gel but not p75NTR-negative fibroblasts. Thus, Pro-Hyp is a low molecular weight growth-initiating factor for specific fibroblasts that is involved in the wound healing process. Pro-Hyp is also supplied to tissues by oral administration of gelatin or collagen hydrolysate. Thus, supplementation of gelatin or collagen hydrolysate has therapeutic potential for chronic wounds. Animal studies and human clinical trials have demonstrated that the ingestion of gelatin or collagen hydrolysate enhances the healing of pressure ulcers in animals and humans and improves delayed wound healing in diabetic animals. Therefore, the low molecular weight fibroblast growth-initiating factor, Pro-Hyp, plays a significant role in wound healing and has therapeutic potential for chronic wounds.